Explore Westonci.ca, the top Q&A platform where your questions are answered by professionals and enthusiasts alike. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.

[tex]\frac{2+h}{9}+\frac{h-1}{3}=\frac{1}{3}[/tex]

Sagot :

Step-by-step explanation:

Multiply both sides by 9 and you will get

[tex]2 + h + 3(h - 1) = 3[/tex]

or

[tex]2 + h + 3h - 3 = 3[/tex]

Solving for h, we get

[tex]4h = 4 \Rightarrow h = 1[/tex]